Effect of hydrophobic resin following different dentin bondings application on nanoleakage of composite restorations - Mohammad Javad Moghadas; Ehsan Rohani; Sara Majidinia; Najmeh Ojrati; Negin Vatanparast (Tehran University of Medical Sciences, 2019)
Background and Aims: The aim of the present study was to evaluate the effect of applying hydrophobic resin after use of different generation of the bonding systems on nanoleakage. Materials and Methods: 20 third molar teeth were selected. The teeth were randomly divided into 4 groups of 5, each was treated using the fourth, fifth, sixth, and seven generation of dentin bonding. Then, the crown of teeth was sectioned from the CEJ region and each specimen was divided into two halves with mesiodistal cut, one half for the application of dentin bonding without the addition of a hydrophobic resin, and the other for the same dentin bonding by the addition of a hydrophobic resin. Afterwards, the specimens were restotred by composites. After placement of specimens in silver nitrate, the amount of nanoleakage was evaluated by SEM. Data were analyzed using a repeated measurement statistical analysis (α=0.05). Results: The use of hydrophobic resins decreased nanoleakage and range of variations in all groups (P<0.05). This reduction was greater for total-etch dentin bonding. Higher degree of nanoleakage occurred in total-etch dentin bonding in most evaluated areas. In general, Clearfil S³ bond showed the least percent of the nanoleakage. Conclusion: All dentin bonding systems showed some degree of reduction in nanoleakage after hydrophobic layer application and the reduction was greater in Total-etch adhesives systems.